Molecular epidemiology of Enteroviruses and Rhinoviruses in patients with acute respiratory infections in Yaounde, Cameroon. Issue 5 (10th March 2021) - Kenmoe, Sebastien; Sadeuh‐Mba, Serge Alain; Vernet, Marie‐Astrid; Penlap Beng, Véronique; Vabret, Astrid; Njouom, Richard
Abstract: Background: Acute respiratory infections (ARI) are associated with a huge morbidity and mortality worldwide. Rhinoviruses (RVs) and Enteroviruses (EVs) are recognized as leading causes of ARI. Objectives: The present study describes the molecular epidemiology of RVs and EVs in Cameroon over a 3‐year surveillance period. Methods: From September 2011 to October 2014, nasopharyngeal swabs were collected from patients with influenza‐like illness (ILI) and severe acute respiratory infections (SARI). Two sub‐genomic regions of the EVs and RVs were targeted for molecular characterization. These included the most conserved 5′‐untranslated region (5′UTR) and the viral protein 4/viral protein 2 transition region (VP4/VP2). Results: A total of 974 samples were collected. Children ≤5 years accounted for 85.7% (835/974) of all participants. Among them, 160 (16.4%) were positive for RVs and/or EVs. RVs and/or EVs were significantly more identified in ILI compared to SARI patients ( P = .015). Both viruses co‐circulated all year long with a marked increase of occurrence during rainy and cold season. All RV species were found to circulate in Cameroon, with 6, 10 and 6 virus types belonging to the RV‐A, RV‐B and RV‐C, respectively. EV species identified comprised EV‐A (1 Coxsackie virus A5), EV‐B (1 Coxsackie virus A9 and 2 Coxsackie virus B1) and EV‐C (1 EV‐C117). Conclusions: This study indicates a strong year‐round occurrence of EV and RV associated respiratory infections in Cameroon. Molecular characterization identified a wide variety of RVs and EVs in patients with ARI in Cameroon.